East Africa Climate-Smart Villages AR4D Sites: 2017 Inventory - Bonilla Findji, Osana; Recha, John W.M.; Radeny, Maren A.O.; Kimeli, Philip (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2018)
Inventory of CSA practices in East Africa’s Climate-Smart Villages.